2018
DOI: 10.1186/s12903-018-0553-z
|View full text |Cite
|
Sign up to set email alerts
|

Children’s dental fear and anxiety: exploring family related factors

Abstract: BackgroundDental fear and anxiety (DFA) is a major issue affecting children’s oral health and clinical management. This study investigates the association between children’s DFA and family related factors, including parents’ DFA, parenting styles, family structure (nuclear or single-parent family), and presence of siblings.MethodsA total of 405 children (9–13 years old) and their parents were recruited from 3 elementary schools in Hong Kong. Child’s demographic and family-related information was collected thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 34 publications
(42 reference statements)
0
67
1
10
Order By: Relevance
“…Other factors influencing dental anxiety such as temperament, personality factors, and the coping abilities of the child, however, may have influenced the outcome . Also, family‐related factors such as socioeconomic status, family structure, the influence of siblings, and parental anxiety may have influenced the anxiety of the child . The Facial Image Scale that was used in this study as a self‐reported measure of anxiety is shown to have good validity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other factors influencing dental anxiety such as temperament, personality factors, and the coping abilities of the child, however, may have influenced the outcome . Also, family‐related factors such as socioeconomic status, family structure, the influence of siblings, and parental anxiety may have influenced the anxiety of the child . The Facial Image Scale that was used in this study as a self‐reported measure of anxiety is shown to have good validity.…”
Section: Discussionmentioning
confidence: 87%
“…22,23 Also, family-related factors such as socioeconomic status, family structure, the influence of siblings, and parental anxiety may have influenced the anxiety of the child. 24,25 The Facial Image Scale that was used in this study as a self-reported measure of anxiety is shown to have good validity. The FIS is widely used since it gives immediate feedback to the clinician regarding the state anxiety of the child and is quick and simple to administer.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, a significant relationship between parents' and children's DFA has been established in many longitudinal and crosssectional studies, 15,16,[34][35][36] although a recent study contradicted these results. 18 It seems that maternal DA has a substantial effect on the children. A significant positive correlation between mothers' DA and their children's DA has been reported.…”
Section: Clinical Significancementioning
confidence: 99%
“…17 However, Wu and Gao in a recent study from Hong Kong found no association between parental DA and DF in their children. 18 DF can also be transmitted from other members of the family to the child. 14 Classically, it was suggested that exposure to threatening information and cultural thoughts can lead to DF during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover studies have also shown that parents who are fearful and anxious about dental treatments are associated with an increase in the occurrence of caries disease in their children, since they are more resistant to accompany their children to the dentist [4]. Studies reveal a strong association between fear and anxiety among children and parental dental fear with the child's behavior [7,8] which show that parents can contribute to anxiety and fear development in children [6]. For this reason, it is necessary to identify and quantify fear and anxiety in the dental treatment and to monitor its effect [9].…”
Section: Introductionmentioning
confidence: 99%